Is comfort food really good for the soul? A replication of Troisi and Gabriel's (2011) Study 2 - Ong, Lay See; IJzerman, Hans; Leung, Angela K.-Y. (Frontiers in Psychology, 2015)
We report the results of three high-powered replications of Troisi and Gabriel’s (2011) idea that writing about comfort food reduces feelings of loneliness amongst securely attached individuals after a belongingness threat. We conducted our studies amongst a large group of participants (Total N = 649) amongst American (MTurk), Dutch (Tilburg University; TiU), and Singaporean (Singapore Management University; SMU) samples. Participants first completed an attachment style scale, followed by writing two essays for manipulating a sense of belongingness and salience of comfort food, and then reporting their loneliness levels. We did not confirm the overall effect over all three countries. However, exploratory results provide the preliminary suggestion that 1) the comfort food explanation likely holds amongst the American samples (including Troisi & Gabriel’s), but not amongst the TiU and SMU samples, and potentially that 2) the TiU and SMU participants self-regulate through warmer (vs. colder) temperature foods. Both of these should be regarded with great caution as these analyses were exploratory, and because the Ns for the different temperature foods were small. We suspect we have uncovered first cross-cultural differences in self-regulation through food, but further confirmatory work is required to understand the cultural significance of comfort food for self-regulation.